2019
DOI: 10.1155/2019/2070619
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Impaired Social Cognition but Not Seizures by Everolimus in a Child with Tuberous Sclerosis-Associated Autism through Increased Serum Antioxidant Proteins and Oxidant/Antioxidant Status

Abstract: We investigated the effect of the mammalian target of rapamycin (mTOR) inhibitor everolimus on tuberous sclerosis complex- (TSC-) associated autistic symptoms and focal seizures with impaired awareness in a female child with TSC. We further evaluated the relationship between improved autistic symptoms and seizures and increased the serum levels of the antioxidant proteins, ceruloplasmin (Cp) and transferrin (Tf), and oxidant-antioxidant status indicated by the oxidant marker oxidized low-density lipoprotein (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
1
0
1
Order By: Relevance
“…66 A case study has been reported in which everolimus also induced psychosis, 67 but in a previous study, the use of everolimus in children and adolescents with tuberous sclerosis resulted in a decrease in prepulse inhibition, an indicator of psychosis and sensorimotor gating. [68][69][70] In this study, high binding affinities between cyclosporine and everolimus, and the receptors found in this study, were discovered. Now, a study to develop drugs that bind to the corresponding receptors, but have the opposite action through pharmacodynamics, can be considered.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…66 A case study has been reported in which everolimus also induced psychosis, 67 but in a previous study, the use of everolimus in children and adolescents with tuberous sclerosis resulted in a decrease in prepulse inhibition, an indicator of psychosis and sensorimotor gating. [68][69][70] In this study, high binding affinities between cyclosporine and everolimus, and the receptors found in this study, were discovered. Now, a study to develop drugs that bind to the corresponding receptors, but have the opposite action through pharmacodynamics, can be considered.…”
Section: Discussionsupporting
confidence: 56%
“…Everolimus, also an immunosuppressant, is a drug that acts on the mechanistic target of rapamycin and that affects the growth of neural stem cells [ 66 ]. A case study has been reported in which everolimus also induced psychosis [ 67 ], but in a previous study, the use of everolimus in children and adolescents with tuberous sclerosis resulted in a decrease in prepulse inhibition, an indicator of psychosis and sensorimotor gating [ 68 - 70 ]. In this study, high binding affinities between cyclosporine and everolimus, and the receptors found in this study, were discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Ωστόσο τα τελευταία χρόνια υποστηρίζεται ότι η υπερλειτουργία και αποτελεσματικότητα των αναστολέων mTOR στη βελτίωση του νοητικού δυναμικού και ανάπτυξης των εν λόγω ασθενών 465,466. Ωστόσο υπάρχουν περιγραφές περιπτώσεων βελτίωσης συμπτωμάτων ΔΕΠΥ και αυτισμού σε ασθενείς με ΟΣ [467][468][469]. Σε επτά ασθενείς με ΟΣ και νεφρικά αγγειομυολιπώματα που συμμετείχαν σε μία κλινική μελέτη φάσης ΙΙ και λάμβαναν sirolimus παρατηρήθηκε βελτίωση στη μνήμη και τις διοικητικές δεξιότητες 470.…”
unclassified